ANALISIS PENGARUH BENCANA BANJIR DI JAKARTA TERHADAP RETURN INDEKS SAHAM SEKTORAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2000-201 - Natasha, Evelyn; Sumami, Sumami (Research Center and Case Clearing House PPM School of Management, 2015)
This study aimed to analyze the effect of flood that occurred in Jakarta toward the return of sectoral stock indices listed on the Indonesia Stock Exchange in the period 2000-2013. The hypothesis of this study is that there are significant effect of floods occurred in Jakarta toward the return of sectoral stock indices listed on the Indonesia Stock Exchange in the period 2000-2013.The data used in this study are secondary data, daily closing prices of sectoral indices in 2000 and 2013 were obtained from the library of the Indonesia Stock Exchange. While the analysis is the analysis of time series with GARCH models. The results of this study are that there are significant effect of floods occurred in Jakarta toward the return of sectoral indices, which 4 of the 10 sectors in 2002, 3 sector in 2007, and 2 sector in 2013. The sectors that are affected significantly are the consumer goods sector, property and real estate, finance, and trade, services and investment.